Easytrip Information System (ETIS) Backend System / Ching Yu Yu - Ching, Yu Yu (2002)
Easytrip Travel Information System (ETIS) backend processing is my final year thesis project title. ETIS is a Web-based travel information system that build for the local hotels, restaurant and transportation company to promote their services. It also enables the World Wide Web user to get the complete travel information in Malaysia ETIS backend system consists eight modules. There are Member registration and sign in module, Accommodations reservation module, E-partner module, Administrator management module, Report module, Newsletter generating module and Help system module. These modules enable the web administrator to manage membership and partnership leveraging on Internet infrastructure. With this capability, the system is able to provide tightly integrated online real-time reservation, payment transaction, order and electronic information dissemination such as newsletters, events, and bulletin to its members, reports to its partners. System can automatically triggers emails based on member's preference whenever there are any promotions or hot deals by the partners. This report introduces the ETIS backend processing system. It’s defines the objective, significance, scope and project schedule that should be identified before development of this system Beside that, it has a description on the topic studied and researched during the literature research and literature review. In the analysis phase, the Waterfall model with prototyping approach was selected for the development process because the strengths of both the Waterfall model and prototyping can be combined in a single project and reduces the risks involved. The development tool chosen was Microsoft Active Server Pages 3.0 whereas the web server was Internet Information Server 5.0 with back-end database SQL Server 2000. All were deployed on Windows 2000 platform. In design phase, the topics covered are Architecture design, Process design, Database design and Interface design. There are many charts, diagrams, table and figures to show the design.